Toxicological Assessment of Supplemental Zanthoxylum Acanthopodium Essential Oil in Rabbits: Evidence from Haemato-Biochemical and Histopathological Indices - Alagbe J. O.; Anaso, E. U.; Shittu, M. D.; Anuore, D. N.; Emiola, I. A. (American Journal of Biology and Natural Sciences, 2026)
This study investigated the toxicological assessment of supplemental Zanthoxylum acanthopodium essential oil in rabbits: evidence from haemato-biochemical and histopathological Indices. Thirty-two clinically healthy weaner male rabbits of about 7 to 8 weeks with an average initial live weight of 710 ± 0.68 kg were stratified by body weight and randomly allocated to one of four experimental groups (n = 8). The experimental diet consisted of a basal (control) group (0 mL/kg) and three levels of Zanthoxylum acanthopodium essential oil inclusion: 0.5 mL, 1.0 mL, and 1.5 mLper kg DM feed daily. Feed and water were made available at all times, and a completely randomized design was adopted throughout the 14-week experimental period during which rabbits were maintained under standard management conditions. The results suggested that Zanthoxylum acanthopodium essential oil influenced (p<0.05) several haematological parameters. Specifically, haemoglobin, red blood cell, mean corpuscular volume, mean corpuscular haemoglobin, and mean corpuscular haemoglobin concentrations. Conversely, pack cell volume, white blood cell, lymphocytes, monocytes, neutrophils, basophils, and eosinophils levels were not affected by the treatment. In serum analysis, total protein, albumin, globulin, glucose, creatinine, sodium, potassium, alkaline phosphatase, alanine aminotransferase, and aspartate aminotransferase remained stable across all groups (p>0.05); however, a significant effect was observed on cholesterol, calcium, phosphorus, and magnesium levels. Liver histology was not affected by Zanthoxylum acanthopodium essential oil across all treatments, showing no signs of toxicity or degeneration. Furthermore, all blood values remained within the recommended physiological ranges for healthy rabbits. The study concludes that Zanthoxylum acanthopodium essential oil can be safely incorporated into rabbit diets up to 1.5 mL as it supports normal physiological function and maintains liver integrity.